Resistant wheat cultivars of central, peninsular and south India against Nilgiri pathotypes of brown and black rust pathogens - KUMAR, J.; SIVASAMY, M.; NISHA, R. (Indian Phytopathology, 2011)
The Wheat and its pathogens causing black, brown and yellow rust diseases (Puccinia spp.) survive the whole year in Nilgiri hills of south India. The rust pathogens particularly causing black and brown rusts over summering on self sown and off-season sown wheat plants in these hills disseminate with cyclonic winds in the month of November and infect winter sown wheat crop in central and peninsular India. Therefore, cultivars released for central and peninsular India must possess resistance to pathotypes of black and brown rust pathogens prevailing in Nilgiri hills for growing rust free wheat crops in these areas. In the present study, we found that pathotypes 77A (109R31), 77-5 (121R63-1), 77-7(121R127), 77-8(253R31) and 17(61R24) of brown rust pathogen as well as 40A (62G29) and 40-1(62G29-1) of black rust pathogen prevailed in Nilgiri hills. Seven varieties released for central India HI 8498, HI 8381, HI 1544, HI 1531, HI 8627, DL 788-2 and HD 4672 are resistant to the Nilgiri pathotypes of brown and black rust pathogens both at seedling and adult stages. Similarly eleven varieties of peninsular India viz., DDK 1001, DDK 1009 , NIAW 917, DDK 1025, UAS 415, NIAW 34, Raj 4083, HD 2781, K 9644, MACS 1967 and AKDW 2997-16 showed excellent resistance to Nilgiri flora of black and brown rust pathogens at both the stages. Some of the varieties released for cultivation in South hill zone including Nilgiri hills do posses only single genes either Lr19 or Lr24, so there is a need to pyramid more number of genes in these varieties for safer cultivation in rust source areas of hilly Tamil Nadu and southern Karnataka. Such multigenic complex will help in curtailing arisal of new pathogenic mutants in rust inoculum source areas particularly in the Nilgiri hills.